Navigating Islamic Education for National Character Development: Addressing Stagnation in Indonesia's Post-Conservative Turn Era - Hosaini, Hosaini; Ni’am, Syamsun; Khamami, Akhmad Rizqon (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research investigates the role of the Islamic education system in shaping the nation's character and addresses the challenges threatening the progress of Islamic education in Indonesia. Employing a descriptive qualitative approach with a desk research method, the study analyzes the phenomenon through extensive literature, including academic articles, books, and reports. The findings reveal that Islamic education in Indonesia confronts the repercussions of a post-conservative era characterized by the ascendancy of conservative religious interpretations altering the political landscape and education system dynamics. Key challenges include resource constraints, inadequate government attention, and the proliferation of conservative ideologies that marginalize local religious authorities. The repercussions include diminished educational quality, widespread teacher moonlighting, and obstacles to integrating Islamic values into the national education framework. Incidents of sexual violence within Islamic educational settings have further damaged institutional reputations. Nonetheless, Islamic education holds significant promise as a solution for character development in Indonesia through a holistic approach that engages schools, families, and communities. Adequate governmental and societal backing is imperative, involving sufficient resource allocation and policies conducive to innovation in Islamic education. By fostering synergy among schools, families, and communities and embracing a flexible, forward-thinking approach, this initiative aims to cultivate a generation strong in faith, morals, and proficient across various scientific and technological domains, poised to confront global challenges and position Indonesia as a cultured, highly competitive nation on the worldwide stage.